Applications Involving Reduction with Hydrazine — Rapid Potentiometric Method for Chromium(VI)-Analysis of Industrially Synthetic Mixtures - Zaky, M. (Asian Journal of Chemistry, 2010)
A new rapid, reliable and accurate procedure is adopted for estimation of small amounts of chromium based on its reduction with known excess of hydrazine sulphate in acid medium whereupon the chromium(VI) solution is reduced to the chromium(III), and the unreacted hydrazine is determined through oxidation with freshly prepared· ethanolic iodine to produce iodide which is titrated with Hg(II). The method finds application to the determination of the element in some industrially important products.